Protecting Genetic Privacy - Fadhel , Aicha (Journal of Science and Knowledge Horizons, 2025)
The article aims to demonstrate the risks posed by biomedical advances in genetic engineering and the consequences of violations of human dignity and the right to genetic privacy if the processing of individuals’ genetic data is useful in some areas of treatment and scientific research, but it involves more negative, compromising the intangibility of the human body and the specificity of its mountain and genetic information that distinguishes it from others. Therefore, the right to confidentiality of individuals’ genetic data prevented others from violating it as sensitive data and to process it only with their prior consent.